Taba's inductive-thinking model (TITM) and its implementation in secondary mathematics classroom - Radin Muhd Imaduddin bin Radin Abdul Halim (Kulliyyah of Education, 2015)
It had been revealed that Malaysia failed to perform well in PISA 2009+ and 2012 for both cycles as we were positioned at the bottom one-third out of 65 participating countries (ranked 52). On the average, Malaysian students scored 421 (2012) points in mathematics, compared to an average of 494 points in OECD countries. Thus, it raised questions on the level of Mathematical literacy among Malaysian students. Hence, this study examined the effects of Taba's Inductive-Thinking Model (TITM) on mathematical literacy among Malaysian Students. This quasi-experimental study investigated if TITM had an impact on the performance in Mathematical Literacy Instrument, such as in OECD-PISA. This study also determined if TITM provided Thinking Classroom experiences; an experience that has specific learning objectives to increase students' social attitudes, thinking skills, academic skills, and students' basic knowledge. Therefore, pre- and post-test were used via compilation of PISA released items to determine if the students who were taught using TITM instruction yielded significantly greater gains in their level of performance compared to the more traditional teaching method (teacher-directed lecture model). The findings obtained in previous researches revealed that the application of TITM instruction increased students' score in PISA when compared with the students taught via teacher-directed lecture model in learning Mathematics. However, the questionnaire indicated that the usage of TITM did not produce a significant difference in students' social attitudes, but it produced a positive change in both thinking and academic skills. Moreover, none had investigated this model in the mathematics field since the model was designed in a social science background. Therefore, this study would benefit learners who prefer the constructivist learning style. It would also benefit educators who need to develop a thinking classroom in their instructional styles. On top of that, this study would further benefit the country as the instructional method might give a positive effect to the level of students' thinking, as well as for the sake of high-stake assessments that involve Malaysia, such as PISA and TIMSS.